Epidemiological characteristics of COVID-19 cases in non-Italian nationals notified to the Italian surveillance system - Fabiani, Massimo; Mateo-Urdiales, Alberto; Andrianou, Xanthi; Bella, Antonino; Del Manso, Martina; Bellino, Stefania; Rota, Maria C; Boros, Stefano; Vescio, Maria F; D'Ancona, Fortunato P; Siddu, Andrea; Punzo, Ornella; et al. (My University, 2021)
BACKGROUND: International literature suggests that disadvantaged groups are at higher risk of morbidity and mortality from SARS-CoV-2 infection due to poorer living/working conditions and barriers to healthcare access. Yet, to date, there is no evidence of this disproportionate impact on non-national individuals, including economic migrants, short-term travellers and refugees. METHODS: We analyzed data from the Italian surveillance system of all COVID-19 laboratory-confirmed cases tested positive from the beginning of the outbreak (20th of February) to the 19th of July 2020. We used multilevel negative-binomial regression models to compare the case fatality and the rate of admission to hospital and intensive care unit (ICU) between Italian and non-Italian nationals. The analysis was adjusted for differences in demographic characteristics, pre-existing comorbidities, and period of diagnosis. RESULTS: We analyzed 213 180 COVID-19 cases, including 15 974 (7.5%) non-Italian nationals. We found that, compared to Italian cases, non-Italian cases were diagnosed at a later date and were more likely to be hospitalized {[adjusted rate ratio (ARR)=1.39, 95% confidence interval (CI): 1.33-1.44]} and admitted to ICU (ARR=1.19, 95% CI: 1.07-1.32), with differences being more pronounced in those coming from countries with lower human development index (HDI). We also observed an increased risk of death in non-Italian cases from low-HDI countries (ARR=1.32, 95% CI: 1.01-1.75). CONCLUSIONS: A delayed diagnosis in non-Italian cases could explain their worse outcomes compared to Italian cases. Ensuring early access to diagnosis and treatment to non-Italians could facilitate the control of SARS-CoV-2 transmission and improve health outcomes in all people living in Italy, regardless of nationality.
Keywords: Comorbidity; Demography; Disease outbreaks; Intensive care unit; Italy; Refugees; Infections; Diagnosis; Economics; Morbidity; Mortality; Traveler; Surveillance; Case fatality rate; Health outcomes; Hospital admission; Delayed diagnosis; Human development index; Sars-cov-2; Covid-19